Emergency responses to COVID-19 and opportunities for inclusive social policy - Martínez Franzoni, J; Sanchez-Ancochea, D (Cambridge University Press, 2024)
This article addresses whether responses to COVID-19 created opportunities for future policy change. We explore this matter by presenting a framework rooted in political economy and the literature on pandemics. We argue that the opportunities created by emergency responses are context-specific and that narratives, policy tools, and pro-equity state actors are variables that mediate emergency responses and future opportunities. We ground our analytical contribution on the emergency cash transfers deployed during 2020 following the COVID-19 outbreak in two contrasting Central American countries, Costa Rica and Guatemala. The paper promotes further policy discussion on the opportunities for progressive change in unequal contexts.